Scrotal calcinosis: A case report - Li, Dan (2010)
Scrotal calcinosis (SC) was a rare and benign condition characterized by multiple calcific substances deposits occurring in scrotum and formed nodules and lumps within scrotal skin. A case of a 49-year-old male patient with a 7-year history of scrotal calcinosis was reported. Histopathological findings had not showed evidences of epithelial structures. In our case, no evidence of cystic structure was found around calcified materials. It was indicated that SC might be idiopathic.